Role of PARP1-interacting protein TRIM44 in the DNA damage response - 김용현 (The Graduate School, Ajou University, 2024)
DNA double-strand breaks (DSBs) are most deleterious to cells and unrepaired DNA breaks cause cell death and genomic instability. To counteract this threat, cells have evolved the defense system to detect DNA damage, signal its presence and mediate its repair, so called DNA damage response (DDR). Two early major regulators of DDR and repair are poly(ADP-ribose) polymerase 1 (PARP1) and ataxia telangiectasia mutated (ATM) kinase. Although each function of these two proteins has been widely studied, their intercorrelations remain elusive. _x000D_ Here, I identified a novel PARP1-interacting protein TRIM44, a member of the tripartite motif (TRIM) family. I found that TRIM44 is recruited to DNA lesions in a PARP1 catalytic activity-dependent manner. I also found that the glutamic acid-rich (GR) domain of TRIM44 is essential for its interaction with PARP1. Functionally, TRIM44 protects the poly-ubiquitin chain of PARP1 via its zinc-finger ubiquitin binding (ZnF UBP) domain, thereby limiting PARP1 hyperactivation after DNA damage. Strikingly, TRIM44 deficiency inhibited the accumulation of ATM and MRN at damaged chromatin, thereby suppressing DSB repair._x000D_ PARP inhibitors (PARPi) are known to inhibit the activity of PARP1 and promote PARP trapping at DNA lesions. PARPi hold promise for the treatment of tumors with homologous recombination (HR) repair defects, but PARPi resistance is still ubiquitous in the clinic. In a clonogenic survival assay, TRIM44 deficiency increased sensitivity to PARPi as efficiently as in BRCA1-deficient cells. Furthermore, PARPi resistance in 53BP1-deficient cells was overcome by TRIM44 depletion. Using data from The Cancer Genome Atlas (TCGA), I identified TRIM44 as an important target in renal clear cell carcinoma (KIRC) and found that sensitivity to DNA-damaging agent was increased in the absence of TRIM44. These data highlight that TRIM44 is an upstream regulator of PARP1 and ATM, and that inhibition of TRIM44 might be a way to significantly increase PARPi sensitivity in various cancers._x000D_ Collectively, these data demonstrate that TRIM44 is recruited to DNA lesions in a PARP1-dependent manner and limits PARP1 hyperactivity by protecting PARP1 ubiquitination. This proper activation of PARP1 by TRIM44 promotes ATM-dependent DDR by inducing recruitment of the ATM and MRN complex to the site of DNA damage. In addition, the absence of TRIM44 increases sensitivity to DNA damaging agent and PARP inhibitor in several cancer cell lines.
학위논문(박사)--의생명과학과,2024. 2
Keywords: ATM; DNA damage response; PARP1; TRIM44; Ubiquitin